MENINGKATKAN HASIL BELAJAR DAN KEMAMPUAN BERPIKIR KRITIS SISWA MELALUI PENERAPAN STRATEGI PEMBELAJARAN BERBASIS MASALAH DI KELAS XI MIPA 4 SMA NEGERI 1 LUBUKPAKAM TAHUN PELAJARAN 2018/2019 - Sitepu, Sabariah (JGK (Jurnal Guru Kita), 2021)
Abstract: Improving Students' Learning Outcomes and Critical Thinking Skills Through Application of Problem-Based Learning Strategies in Class Xi Mipa 4 Sma Negeri 1 Lubukpakam 2018/2019 Academic Year. This action research aims to determine the improvement of learning outcomes and students' critical thinking skills in Biology subjects with the implementation of problem-based learning strategies in class XI MIPA 4 SMA Negeri 1 Lubukpakam in the 2018/2019 school year. The subjects of this study were students of class XI MIPA 4 SMA Negeri 1 Lubukpakam for the 2018/2019 academic year, totaling 36 people. The implementation of this research was carried out in two cycles, with stages: planning, action, observation, and reflection. The data obtained in the form of learning outcomes, critical thinking skills and observation sheets of learning activities. From the results of research in cycles I and II, it shows that: (1) the average value of student learning outcomes in Biology subjects has increased in each cycle, namely: cycle I = 74.44, cycle II = 81.67, and learning mastery has an increase in each cycle, namely the first cycle = 75.00% (27 people), the second cycle = 88.89% (32 people); (2) the average value of students' critical thinking skills increased in each cycle, namely: cycle I = 73.06, cycle II = 80.00, and the completeness of students' critical thinking skills increased in each cycle, namely cycle I = 72.22 % (26 people) and cycle II = 86.11% (31 people). The conclusion of this study is that problem-based learning strategies have a positive effect on improving student learning outcomes and critical thinking skills in Biology subjects in class XI MIPA 4 SMA Negeri 1 Lubukpakam 2018/2019 academic year.
Keywords: Learning Outcomes; Critical Thinking Ability; Problem Based Learning Strategies